Implementasi Model Examples Non Examples Untuk Meningkatkan Hasil Belajar Muatan IPA Subtema Suhu Dan Kalor - Pandit Gustanu (CV. ULIL ALBAB CORP, 2021)
This study aims to describe (1) the application of the exsamples non-exsamples learning model, and (2) student learning outcomes. The subjects of this study were the fifth grade students of SDN Wonorejo 1, totaling 20 students. This study uses a classroom action research design developed by Kemmis & Taggart. The data collection method used is observation, tests, interviews and documentation. The criteria for the success of the actions that have been determined in this study are if student learning outcomes reach 80% of all students who have high learning outcomes. The results of data analysis showed in the first cycle that (1) the results of observing the implementation of learning reached 81%, (2) student learning outcomes in science learning reached 81%. The data in the first cycle has not reached the criteria for the success of the action, so it is necessary to carry out improvements in the second cycle. The results of the second cycle of data analysis showed that (1) the results of observations on the implementation of learning by teachers reached 100%. The results of data analysis from cycle II have exceeded the criteria for the success of the actions that have been determined.